A quantitative study of the relationships between second language (L2) learners’ characteristics and their academic English writing performance - Jin, K (2020)
While interest in L2 writing research has increased substantially in recent years, research on learner’s characteristics (e.g., individual differences, learning strategies and socio-psychological factors) remains relatively scarce. Drawing on the theoretical framework of L1 negative transfer, socio-cognitive orientation and social and emotional learning (SEL) theory, this dissertation develops an operational definition of learner characteristics and explores the relationships between L2 learners’ characteristics and their academic English writing performance. This research project was based on a questionnaire survey to 229 undergraduate students at one public university in Shanghai, China, with results analysed statistically (multiple and hierarchy regression). Participants’ essays were assessed by holistic ratings of wiring quality. The findings from this research showed that many variables such as individual differences (i.e. year of study, English and writing proficiency), learning strategies (i.e. writing teachers, overseas study, editing and proofreading) and socio-psychological factors (i.e. writing self-confidence and anxiety, teaching and learning context) significantly predicted participants’ academic writing performance. The main conclusion to be drawn from this research was that L2 learners’ individual differences explained the greatest amount of variation in their writing scores. In terms of methodological approach, this dissertation recommends that future work should conduct in a qualitative or mixed-methods way to explore L2 learner’s ideology of academic writing in depth. Further, this dissertation suggests that future studies should consider taking ESL context into account so that a more comprehensive study involving all conceptual L2 learners is included. Discussion including a comparison to previous literature and pedagogical implications were also discussed.